2-Mercaptobenzothiazole corrosion inhibitor deposited at ultra-low pressure on model copper surfaces. (15th April 2020) - Wu, Xiaocui; Wiame, Frédéric; Maurice, Vincent; Marcus, Philippe
Highlights: 2-MBT bonds to metallic Cu via S atoms and decomposes partially at room temperature. 2-MBT is lying flat in the monolayer on metallic Cu prior to forming multilayers. Pre-oxidation prevents decomposition and accelerates the initial growth of 2-MBT. 2-MBT decomposes and partially desorbs to give atomic S when annealed above 100 °C. A pre-adsorbed monolayer of 2-MBT on metallic Cu inhibits surface corrosion. Abstract: Adsorption of 2-mercaptobenzothiazole (2-MBT) at ultra-low pressure and room temperature on metallic and pre-oxidized Cu(111) surfaces and its thermal stability were investigated using X-ray photoelectron spectroscopy in order to better understand the interfacial corrosion inhibiting properties. 2-MBT is lying flat in the monolayer with two sulphur atoms bonded to Cu and decomposes partially yielding atomic sulphur when interacting with metallic copper prior to forming molecular multilayers. Decomposition is prevented by surface pre-oxidation with 2D oxide dissociation accelerating the 2-MBT initial adsorption kinetics. 2-MBT further decomposes and partially desorbs above 100 °C. A pre-adsorbed 2-MBT monolayer on metallic copper inhibits surface corrosion.